La difficile construction de l’identité professionnelle des professeurs-documentalistes de l’enseignement agricole public - Jean-François Marcel; Cécile Gardiès (Recherches en Éducation)
The double component of the librarian’s work in agricultural education invites us to question the elaboration processes of professional identity. From a theoretical point of view, our analysis leans on two processes contributing to producing professional identities through a common mechanism, the “identity bargaining”. The “categories of identity analysis” and the “elementary forms of professional identity” (Dubar) are also conveyed. The positioning of the librarians compared to other teachers in the school is understood through the distinction Strauss proposes between “segments” and subgroups constituted by “fellowship circles”. An active research , the purpose of which was to analyze professional activities of a librarian that would have been “forgotten” in prescriptions, allows us to highlight three analysis elements of the professional identity construction: the library as a subjective transaction area, the librarians as a fellowship circle and at last, the relation to the job as an “identity bargaining” area. Three interconnected identity figures (Janus as a tutelary figure, Sysiphus in the background and at last the rising figure of the resilient) stand between “inherited identity”, “attributed identity” and “pursued identity” but clearly testify the tension between those three poles.